A Weak Convergence Theorem for Common Fixed Points of Two Nonlinear Mappings in Hilbert Spaces - Takanori Ibaraki; Shunsuke Kajiba; Yukio Takeuchi (Abstract and Applied Analysis)
In this paper, by using properties of attractive points, we study an iteration scheme combining simplified Baillon type and Mann type to find a common fixed point of commutative two nonlinear mappings in Hilbert spaces. Then, we apply the obtained results to prove a new weak convergence theorem.